Spezialstationen für Patienten mit kognitiver Einschränkung: Ergebnisse einer Umfrage in Kliniken fürGeriatrie in Deutschland = Special care units for patients with cognitive impairment : results of a nationwide survey in geriatric hospitals in Germany - Zieschang, Tania; Bauer, Jürgen M. (Zeitschrift für Gerontologie und Geriatrie, 2019)
BackgroundA large number of older acutely ill patients with cognitive impairment are treated in geriatric care units. Since 1990 some geriatric departments in Germany have established special care units (SCU) for this patient population. In 2010 the first inventory of SCUs in Germany was carried out, which was not based on a nationwide systematic survey.ObjectiveNationwide systematic survey of SCUs for patients with cognitive impairment in geriatric institutions in Germany.MethodsAn online questionnaire (SurveyMonkey®, San Mateo, CA, USA) was sent to all heads of geriatric departments that provide advanced education in geriatric medicine of at least 12 months as registered by the German Society for Geriatric Medicine (DGG).ResultsThe questionnaire was sent to 495 geriatric institutions of which 161 answered (response rate 32.5%). Additionally, 13 institutions answered through a weblink sent in a newsletter by the DGG. In 2017 a total of 42 SCUs existed with a mean size of 13.5 ± 4.7 beds. A further 15 hospitals plan to install an SCU in the near future, 5 probably in 2018. In four geriatric departments an existing SCU was closed down. All SCUs implemented special architectural, structural and personnel measures as recommended by the position paper of the DGG. The few conducted evaluations indicated beneficial results for mobility and disruptive behavior.ConclusionIn recent years the number of SCUs has increased considerably. A methodologically sound evaluation with respect to patient-related outcomes including follow-up and cost-effectiveness is lacking and should be carried out in the near future.
Online publiziert: 3. September 2018
Gesehen am 09.12.2019